Dietary supplementation of Kigelia africana fruits to rabbit bucks fed cottonseed meal on digesta pH and digesta microbial population - Akanbi, O. J.; Shittu, M. D. (ADAN JOURNAL OF AGRICULTURE, 2025)
Medicinal plants are abundant in phytochemicals that has significant effects on digestion. This study was carried out to evaluate the effects of dietary supplementation of Kigelia africana fruits (KAF) on digestibility, digesta pH and intestinal microbial populations on rabbit bucks fed cottonseed meals. Sixty rabbit bucks were divided into five groups with twelve replicates in a completely randomized design. Each treatment group had: (T1) 100% SBM - CSM -KAF (T2) 100% CSM- KAF, (T3) 100% CSM + KAF powder, (T4) 100% CSM + KAF extract, (T5) 100% CSM + KAF powder + KAF extract (blend mixtures) Diets were formulated to meet the nutrient requirements for Rabbit bucks and all other management practices were strictly observed. During 84 days feeding trial, feed intake and feacal samples were determined. After, bucks were slaughtered and intestinal digesta samples were collected to assess microbial populations in the stomach and caecum. Microbial populations were determined by 10-fold serial dilution and total coliform count (TCC), Total anaerobic plate count (TAPC), total anaerobic plate count (TAnPC) and fungi coliform counts were determined. Result indicated that digestible crude protein was significantly (P<0.05) lower in bucks without supplementation and those supplemented with KAF powder but significantly (P<0.05) higher in bucks supplemented with extract and blend mixtures. Acidity of digesta significantly (P<0.05) increased in bucks fed CSM diets with or without supplementation. Supplementation of KAF to CSM diets significantly (P<0.05) suppressed intestinal microbial populations but significantly (P<0.05) higher in nonsupplemented. It was concluded that KAF supplementation to CSM improved digestibility but reduced microbial populations in both stomach and caecum.